Stem cells, cancer and MUSASHI in blood and guts - Kharas, Michael G. (Trends Cancer, 2017)
The mammalian MSI family of RNA binding proteins play important roles as oncoproteins in a wide array of tumors including leukemias, glioblastoma, and pancreatic, breast, lung, and colorectal cancers,. Interestingly, the mammalian Msi genes, Msi1 and Msi2 have been most thoroughly investigated in two highly proliferative tissues prone to oncogenic transformation: the hematopoietic lineage and the intestinal epithelium. Despite their vast phenotypic differences, Msi proteins appear to play an analogous role in governing the stem cell compartment in both of these tissues, potentially providing a paradigm for a more broad understanding of Msi function and its oncogenic activities. In this review we focus on MSI function in the blood and the intestine and discuss therapeutic strategies for targeting this pathway.